THE AUTHORITY OF THE NOTARY HONORARY COUNCIL FROM AN ADMINISTRATIVE LAW PERSPECTIVE - Nur, Muhammad Bahtiar; Muhjad, Hadin (JILPR Journal Indonesia Law and Policy Review, 2025)
The Authority of the Notary Honorary Council from an Administrative Law Perspective. This study aims to determine and analyze the existence of the Notary Honorary Council within the notary profession. Furthermore, it aims to determine and analyze the authority of the Notary Honorary Council regarding Notaries involved in criminal cases. This legal research uses normative legal research or library legal research. This research is prescriptive in nature. The research approaches used are the Statutory and Conceptual Approaches. The Notary Supervisory Council's role in supervising Notaries before the enactment of Law No. 30 of 2004 was carried out by the Court, as stated in Staatsblad 1860 concerning the Regulations on the Position of Notaries. After Law No. 30 of 2004, supervision of Notaries was carried out by the Regional Supervisory Council. After Law No. 2 of 2014, the Notary Honorary Council was created as a replacement for the Regional Supervisory Council, with the same function: approving or rejecting summonses issued by law enforcement officers for Notaries. The authority of the Notary Honorary Council in criminal proceedings involving Notaries highlights the potential dilemma between the obligation to maintain professional confidentiality and to provide testimony, as well as the problems that arise, especially at the investigative stage, regarding the approval of the Notary's summons. The procedure for summoning a Notary that requires the approval of the Notary Honorary Council has the potential to conflict with the principles of simple, fast, and low-cost justice, as well as the principle of equality before the law.